2023
DOI: 10.1186/s12891-023-06575-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone cement distribution may significantly affect the efficacy of percutaneous vertebroplasty in treating symptomatic Schmorl’s nodes

Abstract: Purpose Percutaneous vertebroplasty(PVP) has been widely used in treating symptomatic Schmorl’s nodes(SNs). However, there were still some patients with poor pain relief. At present, there is a lack of research to analyze the reasons for poor efficacy. Methods Review the SNs patients treated with PVP in our hospital from November 2019 to June 2022, collect their baseline data. Reverse reconstruction software was used to calculate the filling rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The efficacy of PVP treatment lies in artificially accelerating local sclerosis. Inadequate cement distribution may prevent sclerotic bone from surrounding the SN and has been reported to have a negative impact on clinical outcomes such as persistent pain [17]. However, in this case, cement was injected until it reached the upper endplate where the SN is located, and the front and rear cortical edges (cement injection volume: T11, 6 mL; T12, 6 mL; L1, 6.5 mL) (Figure 4).…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy of PVP treatment lies in artificially accelerating local sclerosis. Inadequate cement distribution may prevent sclerotic bone from surrounding the SN and has been reported to have a negative impact on clinical outcomes such as persistent pain [17]. However, in this case, cement was injected until it reached the upper endplate where the SN is located, and the front and rear cortical edges (cement injection volume: T11, 6 mL; T12, 6 mL; L1, 6.5 mL) (Figure 4).…”
Section: Discussionmentioning
confidence: 97%
“…At present, many scholars use a variety of ways and technology efforts to improve the stability of spinal fixation, such as some scholars in the original fixed, on the basis of supplementary anterior fixation, laminar hook and install transverse connector, and more scholars to enhance pedicle screw, pull force, reduce pine, nail and other related complications risk, constantly improve technology [ 29 ]. Bone cement has the advantages of short setting time and high curing stability, and is widely used in the treatment of osteoporosis related diseases [ 30 ]. The study of ERDEM et al [ 31 ] found that the pull-out force of pedicle screws increased significantly when using bone cement strengthening fixation, with an increase of 96–262%, while the lateral bending stiffness of pedicle screws increased by 153%, so this technique was gradually applied by spinologists to the surgical treatment of patients with degenerative diseases of the thoracolumbar spine [ 31 ].…”
Section: Discussionmentioning
confidence: 99%